Increased incidence of non-Hodgkin's lymphoma in inflammatory bowel disease patients on immunosuppressive therapy but overall risk is low. Issue 4 (1st October 2000) - Farrell, R J; Ang, Y; Kileen, P; O'Briain, D S; Kelleher, D; Keeling, P W N; Weir, D G
Abstract : BACKGROUND: There is concern that the incidence of non-Hodgkin's lymphoma (NHL) will rise with increasing use of immunosuppressive therapy. AIMS: Our aim was to determine the risk of NHL in a large cohort of patients with inflammatory bowel disease (IBD), and to study the association between IBD, NHL, and immunosuppressive therapy. METHODS: We studied 782 IBD patients (238 of whom received immunosuppressive therapy) who attended our medical centre between 1990 and 1999 (median follow up 8.0 years). Standardised incidence ratios (SIRs) and 95% confidence intervals (CI) were calculated. Expected cases were derived from 1995 age and sex specific incidence rates recorded by the National Cancer Registry of Ireland. RESULTS: There were four cases of NHL in our IBD cohort (SIR 31.2; 95% CI 2.0–85; p=0.0001), all of whom had received immunosuppressive therapy: azathioprine (n=2), methotrexate (n=1), and methotrexate and cyclosporin (n=1). Our immunosuppressive group had a significantly (59 times) higher risk of NHL compared with that expected in the general population (p=0.0001). Three cases were intestinal NHL and one was mesenteric. Mean age at NHL diagnosis was 49 years, mean duration of IBD at the time of NHL diagnosis was 3.1 years, and mean duration between initiation of immunosuppressive therapy and diagnosis of NHL was 20 months. CONCLUSIONS: Although underlying IBD may be a causal factor in the development of intestinal NHL, our experience suggests that immunosuppressive drugs can significantly increase the risk of NHL in IBD. This must be weighed against the improved quality of life and clinical benefit immunosuppressive therapy provides for IBD patients.